Effect of Dietary Supplementation with Different Oils on Productive and Reproductive Performance of Quail - Al-Daraji, Hazim J.; Al-Mashadani, H.A.; Al-Hayani, W.K.; Mirza, H.A.; Al-Hassani, A.S. (International Journal of Poultry Science, 2010)
To assess the effects of dietary oil source on productive and reproductive traits, sunflower oil, flax oil, corn oil or fish oil were induced in quail diets. One hundred and sixty eight 7 weeks old Japanese quail were randomly assigned to 4 groups (12 males and 30 female each) with 3 replicates per group containing 4 males and 10 females each and fed for 13 weeks (including one week as adaptation period) on a commercial diet supplemented with 3% of sunflower oil (T1), Flax oil (T2), corn oil (T3), or fish oil (T4). The birds received water and feed ad libitum during the study. Results of experiment revealed that dietary supplementation with different sources of oil had no significant effect on male body weight, female body weight and feed consumption of quails. Dietary fish oil at the inclusion level of 3% (T4) recorded the best results (p